PERKAWINAN MASYARAKAT BAJO (STUDI PADA MASYARAKAT BAJO SAMPELA, WAKATOBI) - Awat, Rustam (Jurnal Pendidikan Sejarah, 2024)
The problems in this study: 1) What is the type of marriage in the Bajo Sampela community, 2) What is the procedure for implementing marriage in the Bajo Sampela community. The objectives of this study are: 1) to find out the type of marriage in the Bajo Sampela community, 2) to find out the procedure for implementing the marriage customs of the Bajo Sampela community. This research uses socio-cultural research methods and includes qualitative research that produces analytical procedures that do not use statistical analysis procedures and other quantifications. Data collection in this study consists of three methods, namely: 1) observation, 2) interviews, and 3) literature. The subjects in this research are traditional leaders, community leaders, and marriage actors. The results of this research show that marriage in Bajo Sampela consists of 3 types of marriage, namely: a) massuro (proposal), b) siboa (elopement), c) ngandaka (forced marriage). The procedure for implementing the traditional marriage of Bajo Sampela marriage is: a) massuro, the procedures are: lelepatilao (asking), then massuro (proposal), discussing pananga (dowry) and continued with pangarintanga allau allo (determining a good day), then the opening and the wedding ceremony. b) siboa (eloping), the procedure is: the two run away to the customary leader's house, report to the customary leader, notification to both families concerned, discussing the dowry as well as the good day, a simple marriage. c) ngandaka (forced marriage), the procedure is: If caught, the young people are arrested, taken to the village priest's house, and married off, or if they want to be arranged by the adat leader, they are reported first to his family